TINJAUAN HUKUM PELELANGAN BENDA BERHARGA MUATAN KAPAL TENGGELAM (BMKT) - Vinca Pretylia (Universitas Bengkulu, 2017)
Shipwrecks in Indonesian waters have potential of valuable objects, called Vessels of Sinking Vessels (BMKT), in the appointment of BMKT require high costs, so the government must collaborate with investors. The problems formulated in this study relate to what is the legal basis in the Auction of Vessels of Sinking Vessels (BMKT). The purpose of this research is to obtain comprehensive knowledge about the legal arrangements related to the auction of valuable objects containing sinking vessels (BKMT). This research is a normative legal research using secondary data. The results of this study, there is an inventory of the rules regarding BMKT and there are actions taken by the Indonesian government related to the BMKT case in Indonesia, namely establishing the BMKT Moratorium and the issuance of Presidential Regulation Number 44 Year 2016 concerning List of Closed Business Fields and Business Fields Open with Requirements in the Field of Investment stating that the Appointment of BMKT as a Closed Business Field.